Analysis and Evaluation of ERP Information System User Satisfaction PT. Bozzetto Indonesia Using Pieces Framework - Muhammad Muslih; Lutfi Wardhiyana; Septian Rheno Widianto (Jurnal Mantik, 2021)
This research will evaluate the ERP application which has implemented in PT. Bozzeto Indonesia. The application of the information system used only by some of department. Some of them are money accounting department, sales marketing, and production department. As known that inside ERP system there are so many modules in it. Every department using different module for inputting the data, to determine the component of information system running well need the evaluation process. this research aimed to evaluate the running system and to analysis the strength and the weakness of ERP PT. Bozzeto Indonesia information system which used Framework pieces by measuring six variables they are performances information/data, economic, control, efficiency, and services. Which has an analysis point is evaluation referential and information system analysis also to determined what is the impact of profit rate that increase in system used for make the company follow up from the business prospect for facing the global defiance. The results of the research show that ERP PT. Bozzeto Indonesia information system that is using by the company has many advantages and strength that support the business company but also found the disadvantages and weakness so that ERP PT. Bozzeto Indonesia information system need to improve.